Influencer Marketing dan Customer Review Terhadap Keputusan Pembelian Konsumen pada Pengguna Shopee - Putra, Ardiansyah; Muhajirin, Muhajirin; Mardian, Irma (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of influencer marketing and customer reviews on consumer purchasing decisions among Shopee users in Bima City, both partially and simultaneously. This study employed a quantitative approach with an associative research design. The population consisted of Shopee users in Bima City who had made purchases through the Shopee platform. The sample comprised 50 respondents selected using purposive sampling based on the criteria of residing in Bima City, having made purchases through Shopee, and being at least 20 years old. Data were collected through a questionnaire using a five-point Likert scale and analyzed using multiple linear regression with the assistance of SPSS. The results show that influencer marketing has a positive and significant effect on purchasing decisions, with a t-value of 2.495 and a significance value of 0.016. Meanwhile, customer reviews do not have a significant partial effect on purchasing decisions, with a t-value of 1.488 and a significance value of 0.143. Simultaneously, influencer marketing and customer reviews have a significant effect on purchasing decisions, with an F-value of 7.751 and a significance value of 0.001. The coefficient of determination (R²) of 0.333 indicates that influencer marketing and customer reviews explain 33.3% of the variation in purchasing decisions, while the remaining 66.7% is explained by other factors outside the research model. Therefore, influencer marketing has a stronger partial role in explaining purchasing decisions among Shopee users than customer reviews.